Traditional Marriage in Islamic Acculturation and Traditions of the Dayak Ngaju Society - Kukuh Wurdianto; Silvia Arianti; Akhmad Syarif; Marni; Theresia Dessy Wardani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to describe the acculturation of Islamic values ​​and local culture in the traditional marriage process of the Dayak Ngaju society in Baun Bango village. The approach in this study uses a historiography research type using an oral history approach method. The data collection technique used is the observation technique, namely a method of collecting data systematically through observation and recording of the phenomena being studied. The data analysis technique also uses data reduction, data presentation, and data verification with the triangulation method, and drawing conclusions. The stages of marriage that come from religious teachings are what experience acculturation with local marriage customs. In its implementation, the Muslim community carries out the marriage contract according to Islam and marries according to customary law. First of all, the Muslim community carries out the proposal stage like the Dayak Ngaju tribe's customs after that they carry out the marriage contract at home or at the KUA by fulfilling the requirements and pillars of marriage. Then on the same day or the next day, they carry out the Dayak traditional marriage which is not carried out properly because it involves beliefs such as leaving the procession that smells of rituals which of course violate the provisions of Islam such as the nyaki palas ritual, mamapas and planting sawang trees. Basically, the mixture of Islamic culture and local culture in the implementation of traditional Muslim marriages can be seen during the proposal process, determining the wedding day, working together, the marawei coming to each house to invite, and the wedding party